2014
DOI: 10.1038/nature13908
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of de novo coding mutations to autism spectrum disorder

Abstract: We sequenced exomes from more than 2,500 simplex families each having a child with an autistic spectrum disorder (ASD). By comparing affected to unaffected siblings, we estimate that 13% of de novo (DN) missense mutations and 42% of DN likely gene-disrupting (LGD) mutations contribute to 12% and 9% of diagnoses, respectively. Including copy number variants, coding DN mutations contribute to about 30% of all simplex and 45% of female diagnoses. Virtually all LGD mutations occur opposite wild-type alleles. LGD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

131
2,796
7
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,325 publications
(3,007 citation statements)
references
References 51 publications
131
2,796
7
18
Order By: Relevance
“…We searched previously published datasets of largescale sequencing studies on the causes of neurodevelopmental disability for other reports of de novo KCNQ5 mutations and found c.867G>T (p.Lys289Asn), c.1328G>A (p.Arg443Gln), and c.1727A>G (p.His576Arg) in the supplemental data from 820 probands in Lelieveld et al 17 However, these variants were not identified as candidate causes of neurodevelopmental disability in the course of the authors' statistical analyses. The largest currently published cohort of individuals with developmental disorders (the Deciphering Developmental Disorders study, n ¼ 4,293) did not feature any KCNQ5 de novo variants, 18 nor were any included in the data from the cohort of 2,508 autism probands from Iossifov et al 19 Because of the above evidence associating KCNQ5 mutations with neurodevelopmental disorders, as well as prior evidence that mutations in KCNQ2 (encoding Kv7.2) and KCNQ3 (encoding Kv7.3) most likely cause neurological disease via reduced basal M-current (and subsequent neuronal hyperexcitability), 20 the impact of each mutation was characterized in vitro. Figure 2 shows that heterologous expression of homomeric WT Kv7.5 channels yielded voltage-dependent K þ currents that activated slowly upon depolarization with a V 1/2 of activation of À46.2 5 1.8 mV (n ¼ 7), as has been described previously.…”
Section: Resultsmentioning
confidence: 99%
“…We searched previously published datasets of largescale sequencing studies on the causes of neurodevelopmental disability for other reports of de novo KCNQ5 mutations and found c.867G>T (p.Lys289Asn), c.1328G>A (p.Arg443Gln), and c.1727A>G (p.His576Arg) in the supplemental data from 820 probands in Lelieveld et al 17 However, these variants were not identified as candidate causes of neurodevelopmental disability in the course of the authors' statistical analyses. The largest currently published cohort of individuals with developmental disorders (the Deciphering Developmental Disorders study, n ¼ 4,293) did not feature any KCNQ5 de novo variants, 18 nor were any included in the data from the cohort of 2,508 autism probands from Iossifov et al 19 Because of the above evidence associating KCNQ5 mutations with neurodevelopmental disorders, as well as prior evidence that mutations in KCNQ2 (encoding Kv7.2) and KCNQ3 (encoding Kv7.3) most likely cause neurological disease via reduced basal M-current (and subsequent neuronal hyperexcitability), 20 the impact of each mutation was characterized in vitro. Figure 2 shows that heterologous expression of homomeric WT Kv7.5 channels yielded voltage-dependent K þ currents that activated slowly upon depolarization with a V 1/2 of activation of À46.2 5 1.8 mV (n ¼ 7), as has been described previously.…”
Section: Resultsmentioning
confidence: 99%
“…1 Individuals 7 and 8 were identified in a large multicenter study to establish the contribution of de novo coding mutations to autism spectrum disorder. 18,19 Apart from the de novo mutation in WAC these two patients were not reported to have additional de novo mutations. 19 Database searches for copy number variations disrupting WAC We systematically searched for individuals with small deletions including WAC in our in-house database and international databases such as the database of the European Cytogeneticists Association Register of Unbalanced Chromosome Aberrations (ECARUCA) and the Database of Chromosomal Imbalance and Phenotype in Humans using Ensembl Resources (DECIPHER).…”
Section: Diagnostic Exome Sequencingmentioning
confidence: 90%
“…The MYO9B gene was also identified in an ASD whole-exome sequencing study and subsequent TADA analysis as a gene strongly enriched for variants likely to affect ASD risk 43 . Whole exome sequencing applied to families with an ASD child revealed de novo missense mutations in MYO9B leading to an amino acid change in the RhoGAP domain 118 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Knocking out SrGAP3 decreases the number of dendritic filopodia in early development, and it is therefore plausible that SRGAP3 deficiency also leads to decreased dendritic spine density in human patients 255 . Two de novo missense variants in the SRGAP3 gene (one predicted to be probably damaging, and the other predicted to be possibly damaging) were identified in ASD probands from the Simons Simplex Collection 118 . In addition, the authors reported a de novo point mutation E469K (glutamic acid to lysine), which changed negatively charged glutamate to positively charge lysine at the end of the iF-BAR domain.…”
Section: Slit-robo Rho Gtpase-activating Protein 3 (Srgap3) (Srgap3)mentioning
confidence: 99%